Leading by example in a public goods experiment with benefit heterogeneity - Jing Yu; Martin Kocher (Institut für Höhere Studien - Institute for Advanced Studies (IHS), 2020)
Social dilemmas such as greenhouse gas emission reduction are often characterized by heterogeneity in benefits from solving the dilemma. How should leadership of group members be organized in such a setting? We implement a laboratory public goods experiment with heterogeneous marginal per capita returns from the public good and leading by example that is either implemented exogenously or by self-selection. Our results suggest that both exogenous and selfselected leadership only have a small effect on contributions to the public good. We do not find significant differences in contributions for exogenous and self-selected leadership. Leaders seem to need additional instruments to be more effective when benefits are heterogeneous.
Keywords: C91; D03; D64; 330; public goods experiment; heterogeneous benefits; leading by example